Cemaran Timbal (Pb) dan Arsen (As) pada Susu Sapi Perah yang Diberi Pakan Limbah Organik Pasar di Peternakan Sapi Perah Kebon Pedes Bogor - Salundik Salundik; Suryahadi Suryahadi; S.S. Mansjoer; D. Sopandie; W. Ridwan (Universitas Andalas, 2012)
The aims of livestock development is to increase both quality and quantity production, in the same time, ensure the safety of the product. The consumers need to concern about food safety of livestock products because it is related to human’s health. The research was conducted to determine food safety of dairy condition by detecting heavy metal on fresh milk produce by Kebon Pedes Dairy Farm. This research was utilited survey method and cases study and the result analyzed descriptively. The parameters measured are heavy metal Plumbum (Pb) and Arsenic (As) contents by using Atomic Absorption Spectrophotometer (AAS) machine. The result of the study indicated that Pb and As undetected in fresh milk. That’s value lower than standar maxsimum limit according SNI 01-3141-1998 were 0,3 ppm and 0,5 ppm.